ANALISIS PENGARUH RASIO KEUANGAN (SOLVABILITAS, PROFITABILITAS, LIKUIDITAS) TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2014-2018 - Jamiah (stiatabalong.ac.id, 2025)
Company value is the investor's perception of the level of company success, which is closely related to stock prices. High stock prices will increase firm value and market confidence, both in the company's current performance and its future prospects. This study aims to analyze the influence of profitability, liquidity, and solvency on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2018 period.This research uses a quantitative approach with a descriptive research type. The research sample consisted of 19 companies that met the specified criteria. The sampling method used was non-probability sampling with purposive sampling technique. Data were processed and statistically tested. The results showed that partially, the solvency variable had a negative effect on firm value. Meanwhile, profitability and liquidity had no effect on firm value. Simultaneously, the solvency, profitability, and liquidity variables also had no effect on firm value. This study indicates that the data distribution used as a reference in the study is likely not properly distributed. This is because some companies did not present complete financial statement items in the recapitulation of annual financial reports, which ultimately affected the processed data analysis. Keywords: Solvency, Profitability, Liquidity, Firm Value, Banking